Knowledge and attitudes towards the covid-19 vaccine: Conocimientos y actitudes frente a la vacuna contra el COVID-19 - Aguilar Chávez, Pablo V. (2022)
Objective:The objective of this research was to determine the relationship between the level of knowledge and attitudes towards the COVID-19 vaccine in the inhabitants of the province of Trujillo in the year 2021. Materials and methods:The type of study was applied, non experimental desing, with a quantitative approach, cross-sectional, and correlational level; a questionnaire for knowledge and attitudes was administered to a total of 500 adults in the province of Trujillo.   Results: The results show that 88% of the population has a good level of knowledge about the vaccine, and 91% of them have an adequate attitude to be vaccinated.   Conclusions: In this way, it is concluded that there is a significant relationship between the level of knowledge and attitudes towards the vaccine against COVID-19 (p value<0.05).  The level of knowledge is a protective factor (OR: 0.43; CI: 0.2318-0.8053) for an adequate attitude to be vaccinated.